HBV and HBsAg strongly reshape the phenotype, function, and metabolism of DCs according to patients’ clinical stage - Lucile Dumolard; Theophile Gerster; Florent Chuffart; Thomas Decaens; Marie-Noelle Hilleret; Sylvie Larrat; Philippe Saas; Evelyne Jouvin-Marche; David Durantel; Patrice N. Marche; Zuzana Macek Jilkova; Caroline Aspord (Hepatology Communications)
Background:. Hepatitis B is a liver infection caused by HBV. Infected individuals who fail to control the viral infection develop chronic hepatitis B and are at risk of developing life-threatening liver diseases, such as cirrhosis or liver cancer. Dendritic cells (DCs) play important roles in the immune response against HBV but are functionally impaired in patients with chronic hepatitis B. The underlying mechanisms involved in HBV-induced DC dysfunctions remain to be elucidated. Methods:. We explored DC modulations by HBV and HBsAg by exposing blood-derived cDC1s, cDC2s, and plasmacytoid DCs from healthy donors to HBV or HBsAg and stimulating them with toll-like receptor ligand. Their phenotypic and functional features, as well as their metabolic profile, were analyzed through multiparametric flow cytometry and multiplex assays and further explored on patients’ samples. Results:. We found that HBV deeply reshaped the DC secretome in response to toll-like receptor ligand. Strikingly, we observed that HBV-exposed DCs secrete high levels of CX3CL1 (fractalkine), a chemokine responsible for attracting antiviral effectors to the site of infection. HBsAg exposure favored DC activation while drastically altering TRAIL expression in response to toll-like receptor ligand and increasing the secretion of cytokines/chemokines involved in immune tolerance. HBsAg further dampened the metabolism of DC subsets while driving metabolic switches. Notably, the relevance of the CX3CL1/CX3CR1 axis, TGF-β, and metabolic disturbances was demonstrated within intrahepatic DC subsets in patients according to disease stage. Conclusions:. Our work brings new insights into the immunomodulation induced by HBV on DCs, which contribute to impaired antiviral responses and progression toward chronicity.